2015
DOI: 10.1080/21645515.2015.1081726
|View full text |Cite
|
Sign up to set email alerts
|

Temporal trends in hospitalization for rotavirus gastroenteritis: A nationwide study in Italy, 2005–2012

Abstract: AGE severity is linked to etiology, and Rotavirus (RV) accounts for most of severe cases. In 2009 the World Health Organization recommended RV vaccination for all children. Worldwide a number of Countries implemented RV vaccination in their pediatric immunisation programmes, but only a limited number in Europe. This study was designed to estimate the proportion of RVGE among children aged <6 y who were diagnosed with AGE and admitted to hospitals in Italy during the years 2005–2012. A total of 334,982 hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“… 4 An analysis of hospital discharge data from 2005 to 2012 estimated the hospitalization rate for RVGE in children under 6 y old to be 146 and 150 per 100,000 children, as primary and secondary diagnosis, respectively. 2 In the Lombardy region, 50.8% of AGE hospitalizations were found to be due to rotavirus and a further 14% had a possible link to the virus. 5 Both studies found a peak in hospitalization among children under 2 y old.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“… 4 An analysis of hospital discharge data from 2005 to 2012 estimated the hospitalization rate for RVGE in children under 6 y old to be 146 and 150 per 100,000 children, as primary and secondary diagnosis, respectively. 2 In the Lombardy region, 50.8% of AGE hospitalizations were found to be due to rotavirus and a further 14% had a possible link to the virus. 5 Both studies found a peak in hospitalization among children under 2 y old.…”
Section: Introductionmentioning
confidence: 98%
“…Rotavirus vaccines, available since 2006, have been recommended for all children by the World Health Organization (WHO) since 2009 and have been successfully implemented, reducing RVGE incidence and costs, in several European countries and the USA in the last 10 y. 2,8 Recently, a natural experiment took place in Northern Ireland, which has implemented routine rotavirus vaccination, and the Republic of Ireland, with no rotavirus vaccination program. In Northern Ireland, 2 y after introducing vaccination, the incidence of rotavirus infection was reduced by 54% compared with the pre-vaccination era, AGE notifications in the highest risk group (< 2 y old) decreased by 53% and AGE hospitalizations decreased by 40% in children <5 y old.…”
Section: Introductionmentioning
confidence: 99%
“…In Italy, RVGE has an estimated incidence of about 5/100 children <5 years [ 6 ], which was reported to result annually in 320,000 cases handled at home, 80,000 visits to the physician’s office, 10,000 hospitalizations, and 11 deaths [ 7 ]. A recent study found an average annual hospitalization rate for RVGE of 296/100,000 children <5 years, with 81% of cases in the <3 years age group [ 8 ]. The burden of disease is believed to be underestimated by up to 50% [ 8 , 9 , 10 , 11 ] and results in an economic impact of 144 million euros in health and social costs, as well as in overstretching and cluttering emergency departments (ED) and primary healthcare facilities [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Limitations of the study. Using the hospital discharge database as informational flow, some diagnoses could be excluded [32,33,34].…”
Section: Discussionmentioning
confidence: 99%